Teacher Self-Efficacy for Teaching Students With Autism Spectrum Disorder: Associations with Stress, Teacher Engagement, and Student IEP Outcomes Following COMPASS Consultation. (March 2020) - Love, Abigail M. A.; Findley, Jordan A.; Ruble, Lisa A.; McGrew, John H.
Although teachers reporting high teaching self-efficacy demonstrate positive teaching behaviors, minimal stress, and superior classroom management techniques, surprisingly few studies have demonstrated a relationship between teacher self-efficacy and student outcomes. This study explored self-efficacy specific to teaching students with autism spectrum disorder (ASD), and examined relationships with stress, teacher engagement, and student individualized education program (IEP) outcomes. Special education teachers ( N = 44) were recruited as part of a larger study examining a consultation intervention. Results indicated that self-efficacy for teaching students with ASD was significantly and positively correlated with teacher engagement and student outcomes, and negatively correlated with teacher stress. Furthermore, teachers who received the consultation intervention reported higher levels of self-efficacy for teaching students with ASD. This is the first study to report a direct association between teacher self-efficacy and student IEP outcomes and the potential positive impact of a teacher consultation intervention on the teacher intrapersonal factor of self-efficacy.